P01 Severe acute vulval ulceration associated with COVID-19 infection in a sexually active dual COVID-vaccinated young person: a case report. (16th June 2022) - Allstaff, Sarah; Grzybek, Ailie; Nellore, Vimala; Green, Cathy; Bhushan, Yeshi; Ward, Amy; Bradley-Stewart, Amanda; Neill, Caithlin
Abstract : Case: A 20-year old was seen at the height of the Omicron wave of the COVID-19 pandemic with a two day history of a first episode of painful genital ulceration. Her last sexual contact was one week previously. She had no other symptoms and no medical or drug history. There was bilateral inguinal lymphadenopathy and a unilateral 1cm slightly indurated shallow vulval ulcer with slough. She was treated empirically for secondarily infected primary herpes. Three days later she presented with increased pain and negative HSV PCR and STI/BBV tests. She had large bilateral genital ulcers ( figure 1 ) and was admitted. Repeat swabs for HSV, VZV and syphilis were negative. She had a neutrophilia, raised CRP and negative EBV and CMV IgM. A routine nasopharyngeal swab identified SARS-CoV-2 and a full respiratory virus PCR panel was otherwise negative. She disclosed a sore throat and fevers the week before the onset of her vulval symptoms but was reassured by negative home antigen tests. She had received the second dose of an mRNA COVID-19 vaccine four months previously but no booster. She was discharged after five days and treated with a reducing course of oral steroids. At four weeks her ulcers were healing well. Discussion: There are few published cases of Lipschütz ulcers associated with COVID-19 and this case adds to the burgeoning evidence of the possible dermatological manifestations of the disease and crucially it illustrates the value of prompt access to sexual health services during the pandemic.